Mississippi River Tragedies : A Century of Unnatural Disaster - Klein, Christine A., 1956- (Book collections on Project MUSE., 2014)
"American engineers have done astounding things to bend the Mississippi River to their will: forcing one of its tributaries to flow uphill, transforming over a thousand miles of roiling currents into a placid staircase of water, and wresting the lower half of the river apart from its floodplain. American law has aided and abetted these feats. But despite our best efforts, so-called 'natural disasters' continue to strike the Mississippi basin, as raging floodwaters decimate waterfront communities and abandoned towns literally crumble into the Gulf of Mexico. In some places, only the tombstones remain, leaning at odd angles as the underlying soil erodes away. Mississippi River Tragedies reveals that it is seductively deceptive?but horribly misleading?to call such catastrophes 'natural'" -- From Amazon.com.